1990
DOI: 10.1159/000117168
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Uptake Sites and Dopamine Receptors in Parkinson’s Disease and Schizophrenia

Abstract: Dopamine uptake sites, labelled by 3 nM [3H]GBR 12935, were reduced by 28–34% in post-mortem Parkinson’s diseased striata (n = 22) compared to control striata (n = 28). There was no significant difference between post-mortem striata from schizophrenics (n = 16) and controls. Both dopamine D1 and D2 receptors are consistently elevated in Parkinson’s diseased striata from patients who have not been medicated with L-dopa pre-mortem. Both these receptors are down-regulated by L-dopa pre-mortem. In schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 0 publications
2
24
0
1
Order By: Relevance
“…19 The negative results of our meta-analysis are also in line with several postmortem studies of DAT concentration, which reported no alteration in DAT density in striatal tissue of patients with schizophrenia compared with control subjects. 46,47 However it is known that the DAT density decreases as people get older, with a decline in dopaminergic neurons of 4% to 8% per decade in the general population. 48 Some authors have speculated that loss of striatal dopamine terminals can be associated with evolution of the illness from an active phase associated with positive symptoms to a more stable or phase in which negative symptoms dominate the clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…19 The negative results of our meta-analysis are also in line with several postmortem studies of DAT concentration, which reported no alteration in DAT density in striatal tissue of patients with schizophrenia compared with control subjects. 46,47 However it is known that the DAT density decreases as people get older, with a decline in dopaminergic neurons of 4% to 8% per decade in the general population. 48 Some authors have speculated that loss of striatal dopamine terminals can be associated with evolution of the illness from an active phase associated with positive symptoms to a more stable or phase in which negative symptoms dominate the clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…This specificity could be related to the superior clinical efficacy of CLOZ over HAL, because numerous reports have implicated striatal (Pearce et al, 1990), cortical (Goldman-Rakic, 1991Shenton et al, 1992;Selemon et al, 1995), and hippocampal (Luchins, 1990) structures in the pathophysiology of schizophrenia. It is quite possible that Fig.…”
Section: Antipsychotics and Protein Kinase A 205mentioning
confidence: 99%
“…For instance, schizophrenic patients may have greater dopaminergic innervation in the striatum. Regulation of transmitter release, and uptake, could be normal, while greater terminal density could lead to more release of dopamine after re-uptake blockade and vesicular release by amphetamine.Although post-mortem studies have found normal density of presynaptic dopamine markers, such as the dopamine transporter (Hirai et al 1988;Joyce et al 1988;Pearce et al 1990) and expressed mRNA for tyrosine hydroxylase (Ichinose et al 1994), excessive innervation could be obscured by normal aging and more rapid degeneration of terminals in schizophrenia. Dopamine receptors Volkow et al 1996b), transporters (Volkow et al 1996a), and vesicles (Frey et al 1998 all decline with aging, with rates estimated at 2-8% per decade.…”
mentioning
confidence: 99%